The evolution of the European Union’s mediterranean policy - Kaleli, Zeynep (My University, 2010)
Bu tez, Avrupa Birliği’nin Akdeniz’e yönelik olarak geliştirdiği politikalarının “bölgeselleşme” hedefinden uzaklaşarak daha hafif bir işbirliği modeline doğru bir değişim geçirdiği argümanını savunmaktadır. 1995 Euro-Med Ortaklığı ile öngörülen global, kapsamlı işbirliğine dayanan bölgesel politika, yerini 2004 yılındaki Avrupa Komşuluk Politikasıyla farklılaşmış ilişkilere bırakmış ve son olarak, Akdeniz için Birlik girişimi ile somut projelerden oluşan, daha hafif bir işbirliğini temel alan bir politika benimsenmiştir. Bu argümanı savunmak amacıyla tezde, Avrupa Birliği’nin belli başlı Akdeniz politikaları olan “Euro-Med Ortaklığı (1995)”, “Avrupa Komşuluk Politikası (2004)”, ve “Akdeniz İçin Birlik (2008)” politikaları karşılaştırılmalı olarak incelenmiştir.

The main argument of this thesis is that there is a policy shift in the EU’s Mediterranean policies from a global, inclusive and comprehensive region building attempt as in the case of EMP towards a more differentiated relation with the Southern Mediterranean Partner Countries, as in the case of ENP, and finally to a lighter version of cooperation based on concrete projects in the Mediterranean region, as in the case of UfM. To defend this argument, the thesis looks into the EU’s three significant EU policies for tackling the issues of the Mediterranean: namely, the “Euro-Mediterranean Partnership-Barcelona Process (1995)”, “Wider Europe-European Neighbourhood Policy (2004)” and “Union for the Mediterranean (2008)”. It has a comparative approach through which all the three policies are analysed in depth.
Keywords: Avrupa Birliği; Denizcilik Hukuku